Mechanisms regulating cytochrome c release in pancreatic mitochondria. Issue 3 (2nd July 2008) - Odinokova, I V; Sung, K-F; Mareninova, O A; Hermann, K; Evtodienko, Y; Andreyev, A; Gukovsky, I; Gukovskaya, A S
Abstract : Background: Mechanisms of acinar cell death in pancreatitis are poorly understood. Cytochrome c release is a central event in apoptosis in pancreatitis. Here, we assessed the regulation of pancreatic cytochrome c release by Ca 2+, mitochondrial membrane potential (ΔΨm), and reactive oxygen species (ROS), the signals involved in acute pancreatitis. We used both isolated rat pancreatic mitochondria and intact acinar cells hyperstimulated with cholecystokinin-8 (CCK-8; in vitro model of acute pancreatitis). Results: Micromolar amounts of Ca 2+ depolarised isolated pancreatic mitochondria through a mechanism different from the "classical" (ie, liver) mitochondrial permeability transition pore (mPTP). In contrast with liver, Ca 2+ -induced mPTP opening caused a dramatic decrease in ROS and was not associated with pancreatic mitochondria swelling. Importantly, we found that Ca 2+ -induced depolarisation inhibited cytochrome c release from pancreatic mitochondria, due to blockade of ROS production. As a result, Ca 2+ exerted two opposite effects on cytochrome c release: Ca 2+ per se stimulated the release, whereas Ca 2+ -induced depolarisation inhibited it. This dual effect caused a non-monotonous dose-dependence of cytochrome c release on Ca 2+ . In intact acinar cells, cytochrome c release, caspase activation and apoptosis were all stimulated by ROS and Ca 2+, and inhibited by depolarisation, corroborating the findings on isolated pancreatic mitochondria. Conclusions: These data implicate ROS as a key mediator of CCK-induced apoptotic responses. The results indicate a major role for mitochondria in the effects of Ca 2+ and ROS on acinar cell death. They suggest that the extent of apoptosis in pancreatitis is regulated by the interplay between ROS, ΔΨm and Ca 2+ . Stabilising mitochondria against loss of ΔΨm may represent a strategy to mitigate the severity of pancreatitis.